Identification of Resistant Sources to Crown Rust (Puccinia Coronata) in Oat - Omar Abo Baker; Munqez Shtaya (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
This study was conducted to search for new resistant sources to oat leaf rust as well as to characterize the macroscopic components of resistance to crown rust under controlled conditions. One hundred twenty different accessions of oats obtained from the National Small Grains Collection, Idaho (NSGC), USA, in addition to a local susceptible wild accession were used in this study during the growing season of 2008-2009. Disease severity (DS) was calculated three times during the growing season at two week intervals. DS values were used to calculate Area under Disease Progress Curve (AUDPC). The results of this study revealed that the local susceptible (control) accession had 48% DS (100% AUDPC) of leaf rust, and DS for the tested accessions ranged from very high to very low, and the distribution was markedly shifted towards low DS. 50% of the collection showed AUDPC < 50%, while thirteen cultivars. (10.8% of the collection) with AUDPC ≤ 20%, were selected to study their reaction to artificial inoculation with uredio spores of Puccinia coronata at seedling stage. All the tested accessions showed significantly higher relative latency period (RLP) and lower relative infection frequency (RIF) in comparison to the susceptible control. These resistant cultivars were planted in the field to produce grains for further studies.